PERANAN MOTIVASI, KREATIVITAS DALAM PROSES BELAJAR DAN PEMBELAJARAN - Erikasari Erikasari (E-Tech : Jurnal Ilmiah Teknologi Pendidikan, 2019)
The learning process is strongly influenced by the motivation and creativity of students. Low motivation often makes students lazy to learn, less enthusiastic and not creative. Students lack of motivation will cause students to not develop creativity. Students are less able to create something new and tend to imitate what is already seen. Students also don't even have ideas to solve problems. The potential of creative power possessed by individuals as a form of thought in finding relationships between existing elements or new ways of dealing with problems that come from oneself in the form of a strong desire and motivation to create must always be developed. Internal and environmental factors influence the emergence of students' motivation and creativity to learn. One of the characteristics of creative students is being able to create new innovations and try to solve problems with their own abilities. The creativity of a student in learning can be a benchmark for the growth of motivation in a student. The development of motivation and creativity affects the cognitive, psychomotor and affective aspects of students so that they are able to achieve the planned learning goals.